Convincing fashion consumers to go green: a brand communication problem? - Morais, Ricardo (2023)
If it is true that in recent years the concern with climate change has been growing (Bell, Poushter, Fagan & Huang, 2021), there is still a long way to go to make our lifestyles more sustainable. Several companies and brands have been thinking of strategies that allow them to become more sustainable (Hodgson, 2021), albeit with very different levels of success. The fashion industry is, in this context, a very paradigmatic case since it is responsible for the emission of more than "1.2 billion tons of greenhouse gases each year, accounting for more than 10% of the world's carbon footprint" (Motif, 2021). With such a large footprint, several brands and designers have sought to transition to more sustainable fashion. However, despite the efforts made, the truth is that the message does not always reach consumers. Thus, if, in fact, consumers' awareness of the environment and sustainability has grown in recent years, if it is true that consumers have become more demanding in relation to the processes used by brands, we still continue to see a gap between the willingness to buy more sustainable brands and the effective purchase of these brands (Wong, 2021). In this context, consumers are looking for more transparent and sustainable processes and where brands are already working in this direction. For a long time, it was believed that the price prevented the effective purchase of more sustainable products. Still, this idea has been removed in recent years, which leads us to question whether the problem is not in the communication strategies developed by brands to communicate their processes and products. Are consumers aware of what sustainable fashion really means? How have brands been able to convey and explain the difference between concepts such as Ethical Fashion, Circular Fashion, Slow Fashion or Conscious Fashion? Unsure about the effectiveness of this communication, in this work, we seek precisely to analyse how some of the leading brands that are assumed to be sustainable (Abbas & Shipin, 2021; The Good Trade, 2021) have communicated, particularly in social media, spaces that aggregate a large number of consumers, but above all capable of defining trends and habits. On the other hand, these are also the platforms where the new generations are present, gaining even more importance in conveying the message to those who are the consumers of tomorrow and the guarantors of the planet's future.